Genital tuberculosis: current status of diagnosis and management - Yadav, Siddharth; Singh, Prabhjot; Hemal, Ashok; Kumar, Rajeev (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Genitourinary Tuberculosis (GUTB) is the second most common extra-pulmonary manifestation of tuberculosis (Tb) and an isolated involvement of genital organs is reported in 5–30% of the cases. Genital involvement results from primary reactivation of latent bacilli either in the epididymis or the prostate or by secondary spread from the already infected urinary organs. The epididymis are the commonest involved organs affected primarily by a hematogenous mode of spread. Tb is characterized by extensive destruction and fibrosis, thus an early diagnosis may prevent function and organ loss. The gold standard for diagnosis is the isolation and culture of mycobacterium tuberculosis bacilli and in the cases of suspected GUTB, it is commonly looked for in the urinary samples. All body fluid specimens from possible sites of infection and aspirates from nodules must also be subjected to examination. Radiologic investigations including ultrasonography and contrast imaging may provide supportive evidence. Anti-tubercular chemotherapy is the first line of management for all forms of genital Tb and a 6 months course is the standard of care. Most patients with tubercular epididymo-orchitis respond to antitubercular therapy but may require open or percutaneous drainage. Infertility resulting from the tubercular affliction of the genitalia is multifactorial in origin and may persist even after successful chemotherapy. Multiple organ involvement with obstruction at several sites is characteristic and most of these cases are not amenable to surgical reconstruction. Thus, assisted reproduction is usually required. Post treatment, regular annual follow up is recommended even though, with the current multi drug therapy, the chances of relapse are low.